Longitudinal modeling of the relationship between age and maximal heart rate - Gellish, R. L.; Goslin, B. R.; Olson, R. E.; McDonald, A.; Russi, G. D.; Moudgil, V. K. (Medicine & Science in Sports & Exercise, 2007)
Abstract: Purpose: Maximal heart rate (HRmax)-prediction equations based on a person's age are frequently used in prescribing exercise intensity and other clinical applications. Results from various cross-sectional studies have shown a linear decrease in HRmax during exercise with increasing age. However, it is less well established that longitudinal tracking of the same individuals' HRmax as they age exhibits an identical linear relationship. This study examined the longitudinal relationship between age and HRmax during exercise.